Role of Ayurveda in the Management of Dadru W.S.R to Tinea Cruris-A Conceptual Study - Patel, Narsingh; Kadu, Amol; katru, Priyanka (International Research Journal of Ayurveda & Yoga, 2021)
Now a day skin disease is very common at any age of the individual but they are particularly frequent in the elderly. The patient experiences physical, emotional and socio-economic embarrassment in society. Dadru (Tinea) is the type of Kustha (skin diseases) that comes under both due to its quick invading nature and discoloration of skin. As per modern perspective Dadru (Tinea) comes under tinea cruris the most common dermatological manifestation affecting up to 10-20 % of world population. In Ayurveda Samhitas any specific etiology of Dadru (Tinea) has not been explained, except the general etiology of Kustha (skin diseases). Tinea cruris is fungal infection and found more in Male then female. Severe itching and red patches are common dermatological manifestations present in all patients. Fungal culture and KOH are the specific diagnostic method of fungal infection. Panchakarma, Shodhan therapy specially Virechan karma (Purgation) and Raktmokshana (Blood Letting) will help to cure Dadru (Tinea). In present conceptual study we are highlighting the management of Dadru (Tinea) W.S.R to tinea.